STRATEGI PEMBELAJARAN BAHASA INGGRIS YANG MENYENANGKAN UNTUK ANAK USIA DINI - Farida Samad; Nurlela Tidore (Universitas Khairun, 2015)
Early childhood have a sensitive period to learn something, especially learning English. As an English teacher, it is very important to know learning strategy in order to make learning environment more pleasant. That is why the teachers who teach English for young children need some strategies in teaching and learning. There are some strategies that can be applied such as TPR (total physical responsed, songs, music and movement, and stories.